Adsorption behavior and mechanism of Cu(II) onto carbonate-substituted hydroxyapatite in the presence of humic acid. Issue 7 (3rd July 2017) - Wei, Wei; Tian, Zhuangzhuang; Jiang, Ling; Wang, Gang; Cui, Jing; Li, Shiyin; Zhang, Yong; Wei, Zhenggui
ABSTRACT: In this study, adsorption behavior and mechanism of Cu(II) onto carbonate-substituted hydroxyapatite (CHAP) in the absence and presence of humic acid (HA) were studied in batch experiments. The results showed that carbonate incorporation in HAP could significantly enhance the adsorption of Cu(II). In ternary systems, the presence of HA led to an increase in Cu(II) adsorption, dependent on HA concentration. Kinetic studies showed that pseudo-second-order kinetic model better described the adsorption process of Cu(II) onto CHAP and equilibrium data were best described by Sips models. The order of addition sequences of substrates was found to have a noticeable effect on Cu(II) adsorption onto CHAP. The general trend with respect to Cu(II) adsorption being: (CHAP–Cu)–HA > (CHAP–HA)–Cu > (Cu–HA)–CHAP. The present findings were important for estimating and optimizing the removal of Cu(II) ions by using CHA as a potential adsorbent. GRAPHICAL ABSTRACT: